2019
DOI: 10.4236/ojmn.2019.93028
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Schistosomiasis: Report on Seven Adult Patients

Abstract: Background: Spinal Cord Schistosomiasis (SCS) is the most disabling ectopic form of Schistosomal infection. It may or may not have clinical manifestations. They include low back pain and/or lower limb pain and weakness, and double incontinence. Early diagnosis and treatment provide a good outcome. Aim: To describe the clinical, radiologic, and therapeutic data of 7 patients with Spinal Schistosomiasis. Patients and Methods: In this retrospective clinical case study, the medical records of 7 patients with spina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Neuroschistosomiasis is uncommon, and only 800 cases have been reported since its first description in 1930 [9] . S. mansoni primarily is the main cause, with egg deposition in the spinal cord ranging from 0.3% to 13% [17] . Without prompt treatment, the prognosis is poor [2 , 9 , 11] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroschistosomiasis is uncommon, and only 800 cases have been reported since its first description in 1930 [9] . S. mansoni primarily is the main cause, with egg deposition in the spinal cord ranging from 0.3% to 13% [17] . Without prompt treatment, the prognosis is poor [2 , 9 , 11] .…”
Section: Discussionmentioning
confidence: 99%
“…Without prompt treatment, the prognosis is poor [2 , 9 , 11] . Young males are more susceptible as a result of their greater occupational exposure to contaminated water sources [2 , 10 , 16 , 17] . Saleem et al [11] reported SCS in 8 male patients, whose mean age was 16.7 years.…”
Section: Discussionmentioning
confidence: 99%
“…Attaining complete remission requires the use of anti-schistosomal medications as part of medical therapy. Taking all factors into consideration, a high level of suspicion, thorough evaluation, and coordinated care from multiple disciplines are imperative for an accurate diagnosis and successful treatment of spinal schistosomiasis 7 . We hereby present a case of spinal schistosomiasis in a paediatric patient who initially exhibited characteristics resembling a tumour.…”
Section: Introductionmentioning
confidence: 99%